ANALISIS KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA SMP DALAM MENYELESAIKAN SOAL HOTS GEOMETRI BERDASARKAN PRESTASI BELAJAR - Siti Aminah; Ade Rohayati (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
High-level thinking skills are the ability to think in a complex and abstract way about new knowledge then stored in memory, so this knowledge correlates with previous knowledge comprehensively so that it is able to draw its own conclusions. This study aims to analyze and describe the extent of the high-level thinking ability of junior high school students in solving geometry HOTS problems based on learning achievement. This research uses a descriptive qualitative method. The instrument used was in the form of a description test of two HOTS questions on the geometry of flat building materials which refers to the HOTS indicator according to Karthwohl (2002). The subjects of this study are two students from one of the junior high schools in the Indramayu area with different levels of learning achievement, namely students with high and low achievements. The results of the research conducted show that students with high achievement and students with low achievement have not been able to meet the three HOTS Indicators according to Krathwohl (2002), namely analyzing, evaluating and creating. In this study, the level of students' high-level thinking ability is still very low. Therefore, the provision of HOTS-based learning in schools must be applied consistently so that it can encourage the thinking ability of every student, considering that the burden on students is getting heavier in the face of the globalization era and regarding HOTS standard questions that have begun to be used in national exams.